PENINGKATAN KETERAMPILAN BERPIKIR MAHASISWA MELALUI IMPLEMENTASI PERKULIAHAN IPBA BERBASIS SAINS DAN TEKNOLOGI TERINTEGRASI - Oktavianty, Erwina; Hamdani, Hamdani (Jurnal Pendidikan Matematika dan IPA, 2019)
AbstractThis study aims to determine the improvement of students' thinking skills through the Earth and Space Science (IPBA) lectures that integrate science activities with interactive multimedia and local science. The research method used was experimental design (quasy experiment) with comparative group of pretest-posttest group design. Data collection techniques that will be done are measurement techniques in the form of students' thinking skills tests and surveys in the form of student and lecturer responses to the lectures are held. Physics education student semester 4 academic year 2016/2017 will participate as research subject. The results showed that the increase (N-gain) of students' thinking skill in experimental class was 0,70 and control class was 0,40 (both medium category). By using Paired Sample Test obtained tcount = 8,338 at significance level P = 0,000. The significance level is less than 0.05 (P <Î±), so it can be concluded that the application of lectures that integrate local science and technology in IPBA lectures can improve students' thinking skills significantly compared with conventional lectures.Keywords: high order thinking skills, earth and space science, multimedia interaktif.Â